Development of A Self Nanoemulsifying Drug Delivery System for Atenolol using Soybean Oil, Olive Oil and Virgin Coconut Oil - Fitriani, Endang Wahyu; Malini, Helma; Rosita, Vestiana; Handika, Yella (Fakultas Farmasi, Universitas Surabaya, 2025)
Oral formulations remain the primary method of drug delivery, however, the solubility and lipophilicity of compounds such as atenolol present significant obstacles. Atenolol, a β1-selective antihypertensive agent, exhibits limited solubility in both aqueous and gastrointestinal environments. Atenolol is developed in a lipid-based delivery system, specifically the Self-Nanoemulsifying Drug Delivery System (SNEDDS), to enhance its bioavailability and resolve this issue. SNEDDS can improve drug solubility by generating spontaneous nanoemulsions in the gastrointestinal tract. This study aims to evaluate and improve the main components of SNEDDS, specifically oil, surfactant, and co-surfactant, according to the parameters of % transmittance, polydispersity index (PI), and zeta potential. The research findings suggest that the nine formulas have not yet achieved the optimal attributes concerning clarity and durability against dilution. Differences in oil types and amounts of surfactants and cosurfactants influence droplet size, polydispersity index, and zeta potential. Formulas 2 (soybean oil), 7, and 9 (olive oil) exhibit physicochemical parameters that meets the criteria and possess potential for further advancement. Submitted: 10-04-2025, Revised: 22-04-2025, Accepted: 07-05-2025, Published regularly: June 2025